Synthesis and characterization of Palladium(Ii) and Nickel(Ii) complexes of schiff bases and the potential of the Palladium (Ii) complexes as catalysts for C-C bond formation / Amalina Mohd Tajuddin - Mohd Tajuddin, Amalina (Institute of Graduate Studies, UiTM, 2014)
This study reports the synthesis, characterization and catalytic activities of palladium(II) Schiff base complexes, both as homogeneous and MCM-41 supported heterogeneous catalysts for cross-coupling C-C bond formation reactions. Three broad groups of inexpensive Schiff base ligands (L1, L2 and L3) have been synthesized through condensation process between four benzylamine derivatives with aldehyde or ketone in 1:1 molar ratio. 12 ligands and 20 metal complexes of Pd(II) and Ni(II) have been successfully obtained. The metal complexes were prepared through the complexation reaction between the Schiff base ligands with Pd(II) and Ni(II) acetates in a 2:1 molar ratio.